2020
DOI: 10.1097/md.0000000000020108
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of patientsʼ anxiety after a liver or kidney transplantation with functional and self-reported work ability

Abstract: Organ transplantation has become the treatment of choice for end-stage organ failure, including renal and liver failure. The benefits of patient employment after transplantation are numerous, but factors determining the ability to work among these patients are not clearly defined. The growing interest in these factors has strong practical implications for organizations creating vocational rehabilitation programs. Given the interconnection between psychological and physical functioning in patients after transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The majority of transplant recipients are men (65%) [93], while the age distribution amongst patients receiving a transplant shows that 4% is 0-14 years, 44% is 16-55 years, 30% is 56-64 years, and 22% is >65 years old (https://www.eurotransplant.org/statistics/ annual-report/, accessed on 10 January 2022). Some studies have indicated that older [11,28] and female [8] transplant recipients tend to be less physically active, but, interestingly, reported no significant differences in physical activity levels [8,76] or barriers and motivators [11,76] between the different organ transplant recipient groups. One study documented that lung and heart transplant recipients participated more in high levels of physical activity [72], while another study did not identify such differences [8].…”
Section: Sex Age and Transplant Typementioning
confidence: 97%
See 4 more Smart Citations
“…The majority of transplant recipients are men (65%) [93], while the age distribution amongst patients receiving a transplant shows that 4% is 0-14 years, 44% is 16-55 years, 30% is 56-64 years, and 22% is >65 years old (https://www.eurotransplant.org/statistics/ annual-report/, accessed on 10 January 2022). Some studies have indicated that older [11,28] and female [8] transplant recipients tend to be less physically active, but, interestingly, reported no significant differences in physical activity levels [8,76] or barriers and motivators [11,76] between the different organ transplant recipient groups. One study documented that lung and heart transplant recipients participated more in high levels of physical activity [72], while another study did not identify such differences [8].…”
Section: Sex Age and Transplant Typementioning
confidence: 97%
“…The barriers and motivators were classified according to COM-B and TDF (Table 4) and subsequently embedded and discussed below according to the context dimension of CICI. The identified barriers and motivators were related to participation in physical activity and/or exercise [8,11,54,[69][70][71][72][73][74][75][76][77][78][79], exercise-based rehabilitation [80][81][82][83], or participation in the World Transplant Games [84]. The terms physical activity and exercise were often used interchangeably, making it impossible to make a clear distinction between these variables.…”
Section: Leading Question Possible Answermentioning
confidence: 99%
See 3 more Smart Citations